BERLAKUNYA STATUTA FÉDÉRATION INTERNATIONALE DE FOOTBALL ASSOCIATION (FIFA) DIKAITKAN DENGAN KEDAULATAN NEGARA (STUDI KASUS DUALISME PERSATUAN SEPAKBOLA SELURUH INDONESIA (PSSI)) - Hotman Bintang Parulian Aruan; Ningrum Natasya Sirait; Jelly Leviza (Journal of USU International Law, 2014)
ABSTRACT This study aims to determine how the statute owned by an international sports federation which is an international non governmental organizations, Federation Internationale de Football Association (FIFA) on its relation to the sovereignty of a country, and this case is appeared on dualism that happened ini one of FIFA member, Football Association of Indonesia (PSSI). In the dualism of PSSI case, the Indonesian government urged to resolve the problem of PSSI but it is tangent to the articles in the FIFA Statutes which prohibits any intervention, including one from a country through the government, on the problems faced by members of FIFA and if that happens, there will be sanctions provided to the country's football association. The problem in this thesis is how to give FIFA a position as an international organization under international law, how the role of the FIFA Statutes as Lex Sportiva in the international community, and how the FIFA Statutes applicable to the sovereignty of the state in the dualism of PSSI case. The method used is the normative legal research with library research used to obtain secondary data required which includes primary legal materials, secondary and tertiary related issues. The results of the study are presented descriptively in order to obtain an explanation of the issues discussed. The results showed that the FIFA Statutes is Lex Sportiva and applied as a transnational law and binding its members in performing all activities. Applicability of Statutes of FIFA against the sovereignty of the state in the dualism of PSSI indicated by the Indonesian government involvement in resolving the case by holding to the FIFA instructions to guide the parties to the dispute and not to interfere and take PSSI directly. Here it can be seen that the Indonesian government run it with respect to the presence of FIFA and it statutes. FIFA also assumed that the Indonesian government did not intervene in the matter so that it did not issue any sanctions. With the harmonization between the Indonesian government involvement and the enforcement of the FIFA Statutes, PSSI then can solved the dualism problem. Keywords : Statutes, FIFA, FIFA Statutes, State Sovereignty